2014
DOI: 10.1017/s0954579414001151
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid risk factors for major depressive disorder: Are they associated with early onset and recurrent course?

Abstract: Premorbid risk for major depressive disorder (MDD) and predictors of an earlier onset and recurrent course were examined in two studies in a large, community-based sample of parents and offspring, prospectively assessed from late childhood into adulthood. In Study 1 (N = 2,764 offspring and their parents), parental psychiatric status, offspring personality at age 11, and age-11 offspring internalizing and externalizing symptoms predicted the subsequent development of MDD, as did poor quality parent-child relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 157 publications
(274 reference statements)
4
58
0
Order By: Relevance
“…Somewhat surprisingly, parental history of depressive illness and number of prior MDEs were unrelated to recovery or recurrence. However, a recent large, community-based study found that, while parental mood disorder predicted early-onset depression, it did not predict depression recurrence (Wilson et al, 2014). Thus, early-onset, recurrence, and positive familial history may all be alternate indicators of an underlying dimension of depression severity (Burcusa and Iacono, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat surprisingly, parental history of depressive illness and number of prior MDEs were unrelated to recovery or recurrence. However, a recent large, community-based study found that, while parental mood disorder predicted early-onset depression, it did not predict depression recurrence (Wilson et al, 2014). Thus, early-onset, recurrence, and positive familial history may all be alternate indicators of an underlying dimension of depression severity (Burcusa and Iacono, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There also has been an emerging consensus that the combination of early-onset and recurrence represents the most severe form of MDD (Wilson et al, 2014). The high recurrence rate is prognostic information that is useful to patients and clinicians and suggests that preventive interventions should be given priority in the delivery of mental health services; the lowered age for risk of first-onset implies that such services ought to be available to pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…This could be an indication that the early emergence of elevated depressive symptoms carries unique risk for lasting problems, perhaps because early emergence represents a more serious manifestation of depression or because it culminates in an extended period of risk exposure. Factors known to contribute to early onset of depression and risk for later major depressive disorder include parental depression and antisocial behavior, childhood mistreatment, childhood poor academic functioning, early pubertal development, and negative emotionality (Wilson et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Dispositional negativity is also a key risk factor for anxiety disorders, depression, and substance abuse (Clauss & Blackford, 2012; Conway, Craske, Zinbarg, & Mineka, 2016; Grav, Stordal, Romild, & Hellzen, 2012; Hakulinen, Elovainio, et al, 2015; Hengartner, Kawohl, et al, 2016; Kendler & Gardner, 2014; Soldz & Vaillant, 1999; Watson & Naragon-Gainey, 2014; S. Wilson, Vaidyanathan, Miller, McGue, & Iacono, 2014) —psychiatric disorders that are highly prevalent, debilitating, and often challenging to treat (Bystritsky, 2006; Collins et al, 2011; DiLuca & Olesen, 2014; Griebel & Holmes, 2013; Insel, 2012; Kessler, Petukhova, Sampson, Zaslavsky, & Wittchen, 2012; Whiteford et al, 2013).…”
Section: The Nature and Consequences Of Elevated Dispositional Negatimentioning
confidence: 99%